A quality improvement approach to capacity building in low- and middle-income countries. (July 2015) - Bardfield, Joshua; Agins, Bruce; Akiyama, Matthew; Basenero, Apollo; Luphala, Patience; Kaindjee-Tjituka, Francina; Natanael, Salomo; Hamunime, Ndapewa
Abstract : Objectives: To describe the HEALTHQUAL framework consisting of the following three components: performance measurement, quality improvement and the quality management program, representing an adaptive approach to building capacity in national quality management programs in low and middle-income countries. Design: We present a case study from Namibia illustrating how this approach is adapted to country context. Methods: HEALTHQUAL partners with Ministries of Health to build knowledge and expertise in modern improvement methods, including data collection, analysis and reporting, process analysis and the use of data to implement quality improvement projects that aim to improve systems and processes of care. Clinical performance measures are selected in each country by the Ministry of Health on the basis of national guidelines. Patient records are sampled using a standardized statistical table to achieve a minimum confidence interval of 90%, with a spread of ±8% in participating facilities. Data are routinely reviewed to identify gaps in patient care, and aggregated to produce facility mean scores that are trended over time. A formal organizational assessment is conducted at facility and national levels to review the implementation progress. Results: Aggregate mean rates of performance for 10 of 11 indicators of HIV care improved for adult HIV-positive patients between 2008 and 2013. Conclusions: Quality improvement is an approach to capacity building and health systems strengthening that offers adaptive methodology. Synergistic implementation of elements of a national quality program can lead to improvements in care, in parallel with systematic capacity development for measurement, improvement and quality management throughout the healthcare delivery system.